QUALITY OF LIFE ASSESSMENT IN PATIENTS WITH BREAST CANCER AND ITS COMPLICATIONS - Mehraliev, O.Sh. (World of Medicine and Biology, 2022)
To evaluate the effectiveness of the use of quality of life questionnaires in diagnosing and predicting the course of breast cancer, we used questionnaire data using the official versions of the EORTC EQ-5D-5L, QLQ-C30115 questionnaires of patients with breast cancer and metastatic lesions of the lymph nodes, divided into two groups – the main one, 45 patients with metastatic breast cancer with lymph node involvement and the control group, 70 patients without lymph node lesions. When evaluating the results of assessing the patients themselves of their own health status on a visual analogue scale in the main group, the results were significantly higher (81.8±0.27 points and 64.5±0.36 points, respectively, in the control and main groups, р=0.001). The values of the domains “Role functioning” and “Physical functioning”, reflecting the ability to engage in daily duties, results also turned out to be much higher in the control group than in the main group (91.9±1.16 and 77.4±1.92, р= 0.001, 87.9±0.65 and 74.5±1.13, p=0.001, respectively). Thus, studies have shown a pronounced negative effect of lymph node metastases on the psycho-emotional and physical condition of the examined patients.